2010
DOI: 10.1155/2010/149362
|View full text |Cite
|
Sign up to set email alerts
|

A Current Review of Targeted Therapeutics for Ovarian Cancer

Abstract: Difficult to detect, ovarian cancer typically presents at an advanced stage. Significant progress has been achieved in the treatment of ovarian cancer with therapeutics focused on DNA replication or cell division. However, despite sensitivity to induction chemotherapy the majority of patients will develop recurrent disease. Conventional agents for recurrent disease offer little in terms of long-term responses. Various targeted therapeutics have been explored in the management of ovarian cancer. These include m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 94 publications
(105 reference statements)
1
48
0
1
Order By: Relevance
“…Около 80 % случаев РЯ диагностируют на III-IV стадиях болезни. Опухолевый метастатический асцит и плеврит -частые осложнения при РЯ, летальный исход при РЯ в основном связан с распространением метастазов по перитонеальным и / или плевральным поверхностям [16,17]. Исследование асцитической и плевральной жидкости в алгоритме обследования пациенток занимает важное место.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…Около 80 % случаев РЯ диагностируют на III-IV стадиях болезни. Опухолевый метастатический асцит и плеврит -частые осложнения при РЯ, летальный исход при РЯ в основном связан с распространением метастазов по перитонеальным и / или плевральным поверхностям [16,17]. Исследование асцитической и плевральной жидкости в алгоритме обследования пациенток занимает важное место.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…5-10% of ovarian carcinoma patients have a mutation in BRCA-1 and BRCA-2 gene; the lifetime risk of developing ovarian cancer for this gene mutation carriers is 40-50% and 10-20% respectively [50]. Olaparib, Niraparib and Rucaparib are examples of these drugs.…”
Section: Poly-adp-ribose Polymerase (Parp) Inhibitorsmentioning
confidence: 99%
“…There are three aurora kinases as A, B and C which take an active role during the G2-M phase of the cell cyle [50]. Aurora-A is especially important for centrosome functions [57] and Aurora-A is a potential oncogene [58] whose polymorphisms are related with 18-25% increased risk of ovarian cancer additionally breast or colon cancer [59,60].…”
Section: Aurora Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a number of recent studies have indicated that EOC is linked to aberrant cell signaling, including Hedgehog (Hh) and platelet-derived growth factor (PDGF) signaling as well as over-expression of aurora A kinase (AURA) and deregulated expression of the novel tumor suppressor protein, checkpoint with forkhead-associated and ring finger domains (CHFR) [7][8][9][10][11][12][13][14][15][16][17][18][19]. Consequently, targeted agents against Hh pathway components, PDGFR and AURA have been explored recently in the management of ovarian cancer and recurrent disease [20].…”
Section: Introductionmentioning
confidence: 99%